Effect of vibration on power loss of angular contact ball bearings. Issue 5 (6th December 2019) - Zheng, De-Xing; Chen, W.F.; Xiao, Guanyun; Zheng, Dateng
Abstract : Purpose: This paper aims to devote to the experimental analysis and modeling on the heat generation of angular contact ball bearings under vibration. Design/methodology/approach: The experiments about vibration effect on bearing temperature are implemented. To explore the causes of bearing temperature rise, the shaft-bearing system is first simplified to a forced vibration model to analyze the bearing loads in vibration. Next, the vibratory-induced additional load is proposed and the spin power loss of balls is re-derived under vibration. The vibration-induced heat is integrated into a novel forecasting model of bearing power loss. For validation, the muti-node model for angular contact ball bearings is referred to create the thermal network of spindle front bearing, and then the contrast and discussion is done. Findings: The simulation and test results both indicate that more energy is expended and more heat is generated with vibration. And the further quantitative comparisons between simulation results and experimental values of bearing temperature demonstrate the rationality and availability of constructed model on bearing heat generation. Originality/value: The vibration-induced additional load is proposed and modeled, and the novel forecasting model for heat generation for high-speed angular contact ball bearings with vibration is constructed and validated.